Jackpot - Stone, Nic (Crown, 2019)
Meet Rico: high school senior and afternoon-shift cashier at the Gas 'n' Go, who after school and work races home to take care of her younger brother. Every. Single. Day. When Rico sells a jackpot-winning lotto ticket, she thinks maybe her luck will finally change, but only if she--with some assistance from her popular and wildly rich classmate Zan--can find the ticket holder who hasn't claimed the prize. But what happens when have and have-nots collide? Will this investigative duo unite...or divide? Nic Stone, the New York Times bestselling author of Dear Martin and Odd One Out, creates two unforgettable characters in one hard-hitting story about class, money--both too little and too much--and how you make your own luck in the world